2019
DOI: 10.1002/mc.23096
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycoside sensitized hepatocellular carcinoma cells to TRAIL via ROS generation, p38MAPK, mitochondrial transition, and autophagy mediation

Abstract: A major concern in the clinical application of tumor necrosis factor related apoptosis‐inducing ligand (TRAIL) in tumors is the development of resistance. Therefore, agents that can potentially restore TRAIL sensitivity are important therapeutic targets for cancer treatment. Herein, we evaluated lanatoside c and digoxin, both of which are widely used cardiac glycosides (CGs), for their ability to sensitize human hepatocellular carcinoma cells (Huh‐7 and HepG2) through TRAIL‐induced apoptosis. CGs functionalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
(101 reference statements)
1
17
0
Order By: Relevance
“…Ouabain treatment could induce apoptosis through the decrease of intracellular K + and increase of intracellular Na + and Ca 2+ (30)(31)(32), and the suppression of anti-apoptotic and pro-survival genes by STAT3 inactivation could synergistically promote these apoptosis-inducing effects. In addition, it has been shown digoxin and lanatoside C upregulated the ROS generation in hepatocellular carcinoma cells (33), and our data also revealed similar effects in ouabaintreated cancer cells. Ouabain was able to inhibit DNA damage repair directly by the Fanconi anemia/BRCA pathway (34) or indirectly by STAT3 inactivation (35)(36)(37), thus ouabain treatment could remarkably induce DNA double-strand breaks.…”
Section: Discussionsupporting
confidence: 85%
“…Ouabain treatment could induce apoptosis through the decrease of intracellular K + and increase of intracellular Na + and Ca 2+ (30)(31)(32), and the suppression of anti-apoptotic and pro-survival genes by STAT3 inactivation could synergistically promote these apoptosis-inducing effects. In addition, it has been shown digoxin and lanatoside C upregulated the ROS generation in hepatocellular carcinoma cells (33), and our data also revealed similar effects in ouabaintreated cancer cells. Ouabain was able to inhibit DNA damage repair directly by the Fanconi anemia/BRCA pathway (34) or indirectly by STAT3 inactivation (35)(36)(37), thus ouabain treatment could remarkably induce DNA double-strand breaks.…”
Section: Discussionsupporting
confidence: 85%
“…These data indicated that hypoxanthine and guanine degradation were increased or hypoxanthine and guanine synthesis were blocked in Su-DHL4 cells, while level of NADPH for anti-oxidant was elevated in OCI-Ly3 cells. It is well documented that enhanced ROS level is related to apoptosis (Figure 5(A)) [35][36][37][38]. As showed, ROS generation was significantly elevated in Su-DHL4 cells with ouabain rather than in OCI-Ly3 cells (Figured 5(B)).…”
Section: Discussionmentioning
confidence: 69%
“…The catabolism of hypoxanthine and guanine into uric acid produces much ROS [33,34]. Moreover, previous studies showed that ouabain induced cell apoptosis by promoting ROS generation [35][36][37][38]. So we speculated that different antioxidant capacity may contribute to differential apoptosis rate induced by ouabain.…”
Section: Oxidative Stress States and The Effect Of Ouabain In Dlbcl Cmentioning
confidence: 88%
“…The involvement of the ERK/p38 MAPK pathway in the progression of several types of cancer, including glioma, has already been revealed (14). Several oncogenes have been shown to affect the progression and metastasis of multiple types of cancer, including breast, lung and gastric cancer, through this pathway, and numerous drugs targeting the ERK/p38MAPK pathway have been developed or are in clinical trials (15).…”
Section: Introductionmentioning
confidence: 99%